The effects of wearing cold garments on energy expenditure - Hartinger, S.; Porcari, J. P.; Radtke, K.; Doberstein, S.; Hipp. M.; Ryskey, A.; Foster, C. (International Journal of Research in Exercise Physiology, 2017)
Introduction: Stimulation of brown adipose tissue (BAT) by cold exposure purportedly upregulates energy expenditure (EE) and has been suggested as a method to reduce adiposity. BAT in humans is located primarily in the upper torso. Manufacturers have developed garments that contain ice packs and are designed to be worn over these areas. Two such products are the Cool Fat Burner and the Cool Gut Buster. The Cool Fat Burner places ice packs against the shoulders and neck, while the Cool Gut Buster is worn around the abdomen. Purpose: This study was designed to evaluate changes in EE when wearing the Cool Fat Burner and the Cool Gut Buster. Methods: Twenty subjects (12 males; 8 females) sat quietly for a total of 90 minutes while heart rate (HR) and VO2 were recorded. Data collection was separated into three 30-minute phases: rest, low-intensity, and high-intensity. Subjects sat quietly during the rest phase, wore both the Cool Fat Burner and the Cool Gut Buster during the low-intensity phase, and wore both garments and drank cold water during the high-intensity phase. Results: Average VO2 increased significantly across all three phases (rest: 295.6 ± 69.1 ml/min; low-intensity: 333.0 ± 83.2 ml/min; high-intensity: 372.8 ± 87.5 ml/min). When VO2 was converted to EE, it was found that 6 additional kcals were burned in the 30-min low-intensity phase compared to rest (50.1 ± 12.6 vs. 44.1 ± 10.5 kcal) and 11.7 additional kcals were burned during the 30-min high-intensity phase compared to rest (55.8 ± 13.2 vs. 44.1 ± 10.5 kcal). Conclusion: Wearing cold garments resulted in a significant increase in EE. However, the magnitude of the increase may not be practically useful as a weight loss tool.